Architecture and System Design for Marine Cloud Computing Assets. (4th February 2020) - Periola, A A; Alonge, A A; Ogudo, K A
Abstract: The Ocean provides benefits of free cooling for cloud computing platforms. However, the use of the ocean for hosting cloud platforms needs to consider three challenges. The first challenge is identifying suitable underwater locations for siting underwater data centres. The second is designing a low-cost method for acquiring underwater data centres. The third is designing a mechanism ensuring that the use of the ocean for hosting data centres is scalable. This paper proposes the intelligent marine compute locator (IMCL) to identify suitable locations for siting underwater data centres. The proposed IMCL determines the specific heat capacity of different ocean locations at multiple epochs. In addition, the conversion of end-of-life vessels into artificial reefs that host open-source disaggregated hardware computing payload is proposed to reduce acquisition costs. The use of disaggregated architecture enables multiple cloud service providers to use limited ocean locations. The formulated metrics are the power usage effectiveness (PUE) and ocean space utilization (OSU). Simulations show that the use of disaggregated design architecture instead of non-disaggregated architecture (existing mechanism) enhances the PUE and OSU by 4.4 and 16.4% on average, respectively.